Effect of Vapor Pressure Deficit on Gas Exchange in Wild-Type and Abscisic Acid–Insensitive Plants . Issue 4 (27th September 2019) - Cernusak, Lucas A.; Goldsmith, Gregory R.; Arend, Matthias; Siegwolf, Rolf T. W.
Abstract : Altered gas exchange and isotope discrimination in ABA-insensitive poplar with impaired stomata is consistent with unsaturated leaf intercellular vapor pressure at low air vapor pressure deficits. Abstract: Stomata control the gas exchange of terrestrial plant leaves, and are therefore essential to plant growth and survival. We investigated gas exchange responses to vapor pressure deficit (VPD) in two gray poplar ( Populus × canescens ) lines: wild type and abscisic acid–insensitive ( abi1 ) with functionally impaired stomata. Transpiration rate in abi1 increased linearly with VPD, up to about 2 kPa. Above this, sharply declining transpiration was followed by leaf death. In contrast, wild type showed a steady or slightly declining transpiration rate up to VPD of nearly 7 kPa, and fully recovered photosynthetic function afterward. There were marked differences in discrimination against 13 CO2 (Ɗ 13 C) and C 18 OO (Ɗ 18 O) between abi1 and wild-type plants. The Ɗ 13 C indicated that intercellular CO2 concentrations decreased with VPD in wild-type plants, but not in abi1 plants. The Ɗ 18 O reflected progressive stomatal closure in wild type in response to increasing VPD; however, in abi1, stomata remained open and oxygen atoms of CO2 continued to exchange with 18 O enriched leaf water. Coupled measurements of Ɗ 18 O and gas exchange were used to estimate intercellular vapor pressure, e i . In wild-type leaves, there was no evidence of unsaturation of e i, even at VPD above 6 kPa. In abi1 leaves, e i approached 0.6 times saturation vapor pressure before the precipitous decline in transpiration rate. For wild type, a sensitive stomatal response to increasing VPD was pivotal in preventing unsaturation of e i . In abi1, after taking unsaturation into account, stomatal conductance increased with increasing VPD, consistent with a disabled active response of guard cell osmotic pressure.